A mining strategy for minimizing waiting time in blockchains for time-sensitive applications - Ramezan, Gholamreza (2022)
Blockchain, as proposed in Bitcoin, focuses on securing financial transactions. However, in recent years, the use of blockchain has expanded to a wide range of networks and application domains. This includes time-sensitive applications which need transactions to be processed fast enough to meet delay requirements. Reducing the transaction waiting time in the mining process is key to the successful adoption of blockchain in such applications. In this paper, we propose a mining strategy that is aimed at minimizing the average waiting time per transaction by ensuring a certain minimum required block size, based on the average transaction arrival rate, mining service rate, and maximum block size. We derive an expression for the average transaction waiting time of the proposed mining strategy and determine the optimal mining rule. Numerical results show that the average waiting time per transaction can be reduced by up to 15% using the proposed mining strategy compared to the traditional strategy in which miners immediately start the next mining round using the transactions already waiting in the pool.